(3GdbQGFf GdbVGFjI dEKHGJ YOe eTQhYjI GdbQGQ GdeWYhf Hg (B: (3OQGSI ebGQfI (B: (3GdCQOf(B-(3eUQ(B-(3aQfSG (B=s Presumptions of judiciary for proofing the illegality of the challenging decision a comparative study - (3GdWQGhfI, eUWai YHO GdYRjRs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJfGhd cJGH (B((3GdbQGFf GdbVGFjI dEKHGJ YOe eTQhYjI GdbQGQ GdeWYhf Hg (B: (3OQGSI ebGQfI (B: (3GdCQOf(B-(3eUQ(B-(3aQfSG(B) (3hGdPj bGeg HJCdjag (B((3eUWai YHO GdYRjR GdWQGhfI(B) (3jHMK gPg GdcJGH aj GdbQGFf GdbVGFjI dEKHGJ YOe eTQhYjI GdbQGQ GdeWYhf Hg aj GdCQOf, ebGQfI HGdJTQjYGJ GdaQfSjI hGdeUQjI hEbGeI GdOdjd CeGe GdbVGA, HGdWQb GdJj MOOgG GdbGfhf, Ydi hLhO hGbYI bGfhfjI JQJH BKGQgG hbO LGA GdaUd GdKGfj JMJ YfhGf (B: (3eGgjI GdbQjfI GdbVGFjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B247-254.s
Keywords: (3GdCOdI GdbGfhfjIs -- (3GdCQOfs; (3GdCOdI GdbGfhfjIs -- (3aQfSGs; (3GdCOdI GdbGfhfjIs -- (3eUQs; (3GdEKHGJ (B((3bGfhf(B)s -- (3GdCQOfs; (3GdEKHGJ (B((3bGfhf(B)s -- (3eUQs; (3GdEKHGJ (B((3bGfhf(B)s -- (3aQfSGs; (3GdWYf aj GdCMcGes -- (3GdCQOfs; (3GdWYf aj GdCMcGes -- (3eUQs; (3GdWYf aj GdCMcGes -- (3aQfSGs